Keberkesanan jaringan keselamatan sosial (JKS) terhadap kualiti hidup di kalangan masyarakat nelayan Negeri Sulawesi Selatan, Indonesia - , Jamaruddin (2019)
There are various government-funded Social Safety Nets (SSNs) through social assistance funds which have increased annually, yet the rate of poverty fluctuates and the poorest communities are among the traditional fishing communities. This research discusses the effectiveness of SSNs on the quality of life among the poor traditional fishing communities of South Sulawesi. The objective of this study is, firstly, identifying the forms of SSNs which received by the fishermen of the South Sulawesi. Secondly, examining the differences in the quality of life of the fishermen (tiling various demographic variables such as age, ethnicity, education level, monthly income and total liability) before and after receiving SSNs. Thirdly, analyzing the relationship between various forms of SSNs which are free health, free education, poor rice subsidy, direct cash aid and non-financial assistance, towards the quality of life among the fishermen. This research employs quantitative methods through fieldwork and questionnaires on respondents (fishermen) who received the SSNs. There are 322 questionnaires analyzed using descriptive analysis, Paired Sample t Test analysis and Partial Least Square-Structural Equation Modeling (PLSSEM) analysis. The findings show the forms of SSNs received by the fishermen and it also shows that the latter receive subsidies for fuel subsidies, home certificate assistance, home electrical installations, home improvement and business equipment. This study also finds that there is a significant difference in the quality of life of the fishermen before and after receiving the SSNs. Finally, the result of PLS-SEM analysis shows that SSNs have a significant influence of 15% on the quality of life of the fishermen in the South Sulawesi. However, only poor rice subsidies, cash transfer and non-financial aid have significant influence on the quality of life. This study contributes significantly to life of the poor fishermen, which clarifies that SSNs have an important role in improving their quality of life. The SSNs, particularly the direct ones to the fishermen, such as the subsidized rice, the cash assistance and non-cash aids such as fishing gear and skills training, contribute very significantly in improving their quality of life.